Neuroprotective and Antiapoptotic Activity of Lineage-Negative Bone Marrow Cells after Intravitreal Injection in a Mouse Model of Acute Retinal Injury - Anna Machalińska; Dorota Rogińska; Ewa Pius-Sadowska; Miłosz P. Kawa; Edyta Paczkowska; Michał Rudnicki; Renata Lejkowska; Bartłomiej Baumert; Barbara Wiszniewska; Bogusław Machaliński (Hindawi Limited, 2015)
We investigated effects of bone marrow-derived, lineage-negative cell (Lin−BMC) transplantation in acute retinal injury. Lin−BMCs were intravitreally injected into murine eyes at 24 h after NaIO3-induced injury. Morphology, function, and expression of apoptosis-related genes, including brain-derived neurotrophic factor (BDNF) and its receptor, were assessed in retinas at 7 days, 28 days, and 3 months after transplantation. Moreover, global gene expression at day 7 was analyzed by RNA arrays. We observed that Lin−BMCs integrated into outer retinal layers improving morphological retinal structure and induced molecular changes such as downregulation of proapoptotic caspase-3 gene, a decrease in BAX/BCL-2 gene ratio, and significant elevation of BDNF expression. Furthermore, transplanted Lin−BMCs differentiated locally into cells with a macrophage-like phenotype. Finally, Lin−BMCs treatment was associated with generation of two distinct transcriptomic patterns. The first relates to downregulated genes associated with regulation of neuron cell death and apoptosis, response to oxidative stress/hypoxia and external stimuli, and negative regulation of cell proliferation. The second relates to upregulated genes associated with neurological system processes and sensory perception. Collectively, our data demonstrate that transplanted Lin−BMCs exert neuroprotective function against acute retinal injury and this effect may be associated with their antiapoptotic properties and ability to express neurotrophic factors.